Lecture: Bis repetita placent: C. P. E. Bach, W. A. Mozart, and the Practice of Varied Reprises - Beghin, Tom (2024)
Forte/Piano Summer AcademyMusic Department, Cornell University (Ithaca, NY, US)
Abstract: In 1775 Leopold Mozart inquired with Breitkopf in Leipzig whether he might like to print an opus of keyboard sonatas by his son, Wolfgang Amadeus, “in the same manner as those of H: Philipp Carl Emanuel Bach mit veränderten Reprisen.” Pitching Wolfgang’s recently completed Sonatas K 279–284 (1774–75), Leopold may also have intended for his nineteen-year-old son to tap into a potentially lucrative amateur market. The publication did not happen, but the question is intriguing: what might such Mozart Sonatas with Varied Reprises have looked like? Some larger questions emerge. When performing classical keyboard sonatas, what happens when we submit ourselves to the expectation of continuous variation? How do we navigate the materiality of a printed score? What are the limits to incorporating our variants and at what point do we feel like starting over, and re-composing altogether? How do we tap into the eighteenth-century ideal of a keyboardist as composer-performer, while becoming sensitive to a musical culture that harbored a more fluent use of a musical work, tailored to the needs of a performer? These questions will be balanced against an exploration of rhetorical intent behind repetition and variation, Bach’s published thoughts on the matter, and own experiments of teaching and performing Mozart’s sonatas on a Stein fortepiano as the instrument that in 1777 became crucial in the professional life of a maturing improviser and composer.
FRIS
1
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850